Utilizing hygroscopicity of wood as a building skin material for improving thermal comfort a biometric approach for passive and responsive architecture - Latada, Alma Jo C.; Juanga, Jean Marie V. (2019)
Kinetic Architecture is a new emerging concept that aims to reduce building energy use through climate-responsiveness; however, these mechanisms rely on sophisticated technologies, sensors, actuators, control systems, which are energy-dependent. Pine cones? moisture induced expansion offer inspiration to move away from smart building systems and move towards the creation of sustainable, passive, and responsive building materials. This paper explores the possibility of passive and responsive architecture by incorporating hygromorphic building skins that will allow exchange of air and ventilation in buildings. Using species present in the local setting, Gmelina (Gmelina arborea) and Tanguile (Shorea polysperma), the reactivenesss (curvature induced), responsiveness (time response), and rate of transfer of moisture of the created hygromrophs were measured and analyzed.Pine cones? active and passive layers were emulated by using materials that parallels the functions and properties of these layers. Wood laminates were used for the active layer, and fiberglass cloth were used for the passive layer. The two layers were bound together by epoxy resin and were cut according to the designed installation patterns. Three pattern configurations were explored in this research. Pre-conditioning the active layer allowed the creation of hygromorphs with two different configuration: one that opens at high humidity, and one that opens at low humidity. Each of the configurations have different application and function. Experimentations were done inside a climate chamber where moisture and temperature levels were carefully manipulated and measured.Overall, Gmelina showed better performance in terms of curvature, time response, and rate of humidity transfer compared to Tanguile. However, Tanguile?s curvature performance is still considered significant and can still encourage humidity transfer. Excluding durability in the scope of this study, the created responsive hygromorphs can be applied and used to encourage ventilation, and natural lighting to buildings. This presents opportunities for a passive and responsive architecture that adapts to the changing environment.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2019